Walnut green peel-based hard carbon and its preparation method, pole piece and application

By carburizing pretreatment, acid-base treatment and graphite boat contact high-temperature carbonization treatment, the problem of poor electrochemical performance of walnut green skin-based hard carbon is solved, significantly improving its Coulombic efficiency and capacity, and achieving excellent rate performance.

CN119774584APending Publication Date: 2025-04-08SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411982561.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

As the negative electrode material of sodium ion battery, walnut green-skin hard carbon has low efficiency, small capacity and small platform capacity for the first time, resulting in poor electrochemical performance, limiting its application potential.

Method used

By pre-treating the walnut green peel, acid-base treatment, and high-temperature carbonization treatment with the graphite boat, the specific surface area and degree of graphitization of the walnut green peel are significantly improved.

Benefits of technology

The first Coulomb efficiency, large capacity and excellent rate performance of walnut green-skin-based hard carbon has been significantly improved, allowing it to show better electrochemical performance in sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774584A_ABST
    Figure CN119774584A_ABST
Patent Text Reader

Abstract

The present invention provides a walnut green peel-based hard carbon and a preparation method, pole piece, and application thereof. The preparation method of the walnut green peel-based hard carbon comprises the following steps: subjecting the walnut green peel to carbonization pretreatment, alkali treatment, and acid treatment, and then contacting the walnut green peel with a graphite boat for high-temperature carbonization; the terminal temperature of the high-temperature carbonization is 1500°C-1600°C; and the holding time of the high-temperature carbonization is 1h-5h. The preparation method of the walnut green peel-based hard carbon of the present invention performs carbonization pretreatment and acid-base treatment on the walnut green peel powder, and under the effect of the crystal phase epitaxy generated by contact with the graphite boat and high-temperature carbonization treatment, the specific surface area and graphitization degree of the walnut green peel-based hard carbon are significantly improved, and a walnut green peel-based hard carbon with high first coulomb efficiency, large capacity, and excellent rate performance is successfully prepared, which provides a good foundation for the application of walnut green peel-based hard carbon in sodium ion battery pole piece materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to walnut green peel-based hard carbon and a preparation method, a pole piece and application thereof. Background Art

[0002] As a renewable resource, biomass plays an important role in the future energy field due to its rich diversity and wide sources. Biomass not only comes from waste from various fields such as cities, households, agriculture and forestry, but also includes natural resources such as trees, plants, and algae. In the context of growing global energy demand, the development and utilization of biomass resources is particularly important. Biomass is mainly composed of three basic components: cellulose, hemicellulose (long-chain and short-chain polysaccharides) and lignin (a complex phenolic polymer). Among these components, the carbon content is as high as more than 60%, making biomass an ideal precursor for the hard carbon negative electrode of sodium ion batteries. When plant tissue is carbonized, hard carbon with a 3D structure is formed, which provides a channel for electrolytes to enter the interior and provides more sodium channels and storage sites in the generated hard carbon. It is particularly worth mentioning that when the plant cell wall is retained, a pattern called a honeycomb structure appears. This structure acts as a transmission channel for electrolytes in biomass, facilitating the intercalation and deintercalation of sodium ions. For example, biomass materials such as pine pollen, wheat straw, poplar wood, cork and apricot shells all have this unique honeycomb structure, which gives them broad application prospects in the field of sodium-ion battery negative electrode materials.

[0003] In China, walnut, as an important woody oil crop, ranks first in the world in terms of planting area and output, with an annual total output of more than 3 million tons. However, walnut green peel, as the outer peel of walnut, is often discarded as crop waste during the harvest process. With the increasing attention to sustainable resource utilization, walnut green peel as a potential hard carbon raw material has gradually attracted the interest of researchers. However, walnut green peel-based hard carbon, as a negative electrode material for sodium ion batteries, faces the problems of low first coulombic efficiency, small capacity (<300mAh / g) and small platform capacity. The reason is that walnut green peel contains complex chemical components, such as cellulose, lignin and organic acids. These impurities are easily decomposed during the carbonization process, and the ideal disordered graphite layer structure and suitable pore structure cannot be obtained, which affects the purity and structural stability of hard carbon, thereby reducing the electrochemical performance of walnut green peel-based hard carbon and limiting its application potential in sodium ion batteries. Therefore, preparing walnut green peel into walnut green peel-based hard carbon with high first coulombic efficiency, large capacity and excellent rate performance is a technical problem to be solved in this field. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects of low first coulombic efficiency, low capacity (<300mAh / g) and small platform capacity of walnut green peel-based hard carbon as a negative electrode material for sodium ion batteries in the prior art, and to provide a walnut green peel-based hard carbon and its preparation method, pole piece, and application. The preparation method of the walnut green peel-based hard carbon of the present invention performs carbonization pretreatment and acid-base treatment on walnut green peel powder, and under the crystal phase epitaxy produced by contact with a graphite boat and high-temperature carbonization treatment, the specific surface area and graphitization degree of the walnut green peel-based hard carbon are significantly improved, and a walnut green peel-based hard carbon with high first coulombic efficiency, large capacity and excellent rate performance is successfully prepared, which provides a good foundation for the application of walnut green peel-based hard carbon in sodium ion battery pole piece materials.

[0005] The present invention solves the above technical problems through the following technical solutions:

[0006] The present invention provides a method for preparing walnut green peel-based hard carbon, which comprises the following steps:

[0007] The walnut green peel is carbonized after being subjected to carbonization pretreatment, alkali treatment and acid treatment, and then contacted with a graphite boat;

[0008] The end point temperature of the carbonization is 1500°C-1600°C;

[0009] The heat preservation time of the carbonization is 1h-5h.

[0010] Preferably, the walnut green husk is walnut green husk that has been subjected to one or more of a crushing treatment, a screening treatment or a drying treatment.

[0011] More preferably, the crushing equipment is a wall breaking machine.

[0012] More preferably, the median particle size D50 of the product obtained after the pulverization process is 35 μm-45 μm, for example 40 μm.

[0013] More preferably, the mesh size of the sieve used in the screening process is 250-350 mesh, for example, 300 mesh.

[0014] In this scheme, the walnut peel is crushed to a particle size of 35μm-45μm in D50 and further sieved through a sieve to make the raw material more uniform, which helps the structural uniformity in the subsequent carbonization process and improves the capacity and cycle stability of the battery.

[0015] More preferably, the drying equipment is a blower.

[0016] More preferably, the drying temperature is 80°C-120°C.

[0017] More preferably, the drying time is 6 h-24 h, for example 12 h.

[0018] Preferably, the carbonization pretreatment device is a tubular atmosphere furnace.

[0019] Preferably, during the carbonization pretreatment process, the container for holding the walnut peel is an alumina porcelain boat.

[0020] Preferably, the end point temperature of the carbonization pretreatment is 450°C-750°C, more preferably 500°C-600°C.

[0021] Preferably, the atmosphere of the carbonization pretreatment is air.

[0022] Preferably, the heating rate from room temperature to the endpoint temperature of the carbonization pretreatment is 1°C / min-10°C / min, more preferably 2°C / min-5°C / min.

[0023] Preferably, the holding time of the carbonization pretreatment is 1 h to 10 h, more preferably 2 h to 4 h.

[0024] In this scheme, the specific surface area and graphitization degree of hard carbon can be significantly increased by carbonizing the walnut green peel. The carbonization temperature is set at 450℃-750℃, and the graphitization process is controlled by slowly increasing the temperature by 1℃ / min-10℃ / min, which can effectively reduce impurities in the raw materials, thereby improving the purity and stability of hard carbon.

[0025] Preferably, in the alkaline treatment, the concentration of the alkaline solution is 1M-5M.

[0026] More preferably, the concentration of the alkaline solution is 1M-2M.

[0027] More preferably, the alkaline solution is sodium hydroxide or potassium hydroxide.

[0028] Preferably, the temperature of the alkali treatment is 50°C-90°C, more preferably 50-60°C.

[0029] Preferably, the alkali treatment time is 1 h-5 h, more preferably 4 h-5 h.

[0030] Preferably, in the acid treatment, the concentration of the acidic solution is 1M-5M.

[0031] More preferably, the concentration of the acidic solution is 2M-3M.

[0032] More preferably, the acidic solution is hydrochloric acid or sulfuric acid.

[0033] In the present invention, the temperature of the acid treatment is a conventional temperature in the art, such as room temperature.

[0034] Preferably, the acid treatment time is 1 h-6 h, more preferably 5 h-6 h.

[0035] Preferably, the carbonization device is a tubular atmosphere furnace.

[0036] Preferably, the terminal temperature of the carbonization is 1550°C-1600°C.

[0037] Preferably, the carbonization atmosphere is an inert atmosphere, more preferably argon.

[0038] Preferably, the heating rate from room temperature to the end temperature of the carbonization is 1°C / min-8°C / min, more preferably 2°C / min-5°C / min.

[0039] Preferably, the carbonization insulation time is 2h-3h.

[0040] The present invention also provides a walnut green peel-based hard carbon prepared by the preparation method of the walnut green peel-based hard carbon as described above.

[0041] The present invention also provides a pole piece, which comprises the walnut green peel-based hard carbon as described above.

[0042] The present invention also provides an application of the pole piece as described above in an electrochemical device.

[0043] The positive and progressive effects of the present invention are:

[0044] (1) The preparation method of walnut peel-based hard carbon of the present invention significantly improves the quality and performance of walnut peel-based hard carbon through a series of optimization processes. The process of carbonization pretreatment, acid-base treatment, and subsequent high-temperature carbonization in contact with a graphite boat is adopted. The crystal phase epitaxy produced by the graphite boat and high-temperature carbonization significantly improves the specific surface area and graphitization degree of walnut peel-based hard carbon. Such optimization makes the finally obtained walnut peel-based hard carbon have higher electrochemical performance and can play a better role in sodium ion batteries.

[0045] (2) By improving the preparation process, the present invention significantly improves the first coulombic efficiency and capacity of walnut green peel-based hard carbon. After fine-tuning the carbonization process, the prepared walnut green peel-based hard carbon not only exhibits a high coulombic efficiency during the first charge and discharge process, but also makes its capacity exceed 300mAh g-1, overcoming the problem of low capacity of traditional walnut green peel-based hard carbon and meeting the application requirements of high energy density batteries.

[0046] (3) The walnut green peel-based hard carbon prepared by the present invention also has excellent rate performance and can maintain stable electrochemical performance under fast charge and discharge conditions. The excellent performance of the walnut green peel-based hard carbon at high rates enables it to have a good charging rate and a long cycle life in practical applications, fully demonstrating its potential for wide application in high-performance energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the SEM image of the walnut peel-based hard carbon of Example 1.

[0048] Figure 2 The XRD spectra of walnut green peel-based hard carbon of Example 1 and Comparative Example 1 are shown.

[0049] Figure 3 XPS spectra of walnut peel-based hard carbon of (a) Comparative Example 1 and (b) Example 1.

[0050] Figure 4 The first cycle charge and discharge curves of the batteries assembled with walnut green peel-based hard carbon of Example 1 and Comparative Example 1.

[0051] Figure 5 This is a long cycle performance diagram of the battery assembled with walnut peel-based hard carbon of Example 1 and Comparative Example 1.

[0052] Figure 6 This is a rate performance diagram of the battery assembled with walnut peel-based hard carbon of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0053] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0054] Example 1

[0055] (1) The collected walnut green peel was crushed in a wall-breaking machine, passed through a 300-mesh sieve, and the D50 was 40 μm, and then dried in a forced air oven at 80°C for 12 h. 10 g of walnut green peel powder was placed in an alumina porcelain boat, placed in a tubular atmosphere furnace, and heated to 500°C at a rate of 5°C / min in an air atmosphere.

[0056] (2) Take out the walnut green peel after carbonization pretreatment, put it into 1M NaOH solution, and treat it with alkali at 50°C for 5 hours. Then filter, wash and dry. Put the walnut green peel after alkali treatment into 2M HCl solution, stir at room temperature for 5 hours, wash and dry.

[0057] (3) The walnut peel after carbonization pretreatment, alkali treatment and acid treatment was placed in a graphite boat, placed in a tubular atmosphere furnace, and heated to 1550°C at a rate of 2°C / min under an argon atmosphere. The carbonization was performed for 2 hours and the mixture was naturally cooled to room temperature to obtain walnut peel-based hard carbon.

[0058] Comparative Example 1

[0059] (1) The collected walnut green peel was crushed in a wall-breaking machine, passed through a 300-mesh sieve, and the D50 was 40 μm, and then dried in a forced air oven at 80°C for 12 h. 10 g of walnut green peel powder was placed in an alumina porcelain boat, placed in a tubular atmosphere furnace, and heated to 500°C at a rate of 5°C / min in an air atmosphere.

[0060] (2) Take out the walnut green peel after carbonization pretreatment, put it into 1M NaOH solution, and treat it with alkali at 50°C for 5h. Then filter, wash and dry. Put the walnut green peel after alkali treatment into 2M HCl solution, stir it at room temperature for 5h, then filter, wash and dry.

[0061] (3) The walnut peel that had been carbonized, treated with alkali, and treated with acid was placed in an alumina boat, placed in a tubular atmosphere furnace, and heated to 1550°C at a rate of 2°C / min under an argon atmosphere. The mixture was carbonized for 2 hours and naturally cooled to room temperature to obtain walnut peel-based hard carbon.

[0062] Comparative Example 2

[0063] (1) The collected walnut green peel was crushed in a wall-breaking machine, passed through a 300-mesh sieve, and the D50 was 40 μm, and then dried in a forced air oven at 80°C for 12 h. 10 g of walnut green peel powder was placed in an alumina porcelain boat, placed in a tubular atmosphere furnace, and heated to 500°C at a rate of 5°C / min in an air atmosphere.

[0064] (2) Take out the walnut green peel after carbonization pretreatment, put it into 1M NaOH solution, and treat it with alkali at 50°C for 5 hours. Then filter, wash and dry. Put the walnut green peel after alkali treatment into 2M HCl solution, stir at room temperature for 5 hours, wash and dry.

[0065] (3) The walnut peel after carbonization pretreatment, alkali treatment and acid treatment was placed in an alumina boat, placed in a tubular atmosphere furnace, and heated to 1300°C at a rate of 2°C / min under an argon atmosphere. The mixture was carbonized for 2 hours and naturally cooled to room temperature to obtain walnut peel-based hard carbon.

[0066] Comparative Example 3

[0067] (1) The lignite was crushed in a wall-breaking machine, passed through a 300-mesh sieve, and the D50 was 40 μm, and then dried in a forced air oven at 80°C for 12 h. 10 g of lignite powder was placed in an alumina porcelain boat, placed in a tubular atmosphere furnace, and heated to 500°C at a rate of 5°C / min under a nitrogen atmosphere.

[0068] (2) The lignite powder after carbonization pretreatment was taken out, placed in a 2M HCl solution, stirred at room temperature for 5 h, filtered, washed, and dried.

[0069] (3) The lignite after carbonization pretreatment and acid treatment was placed in a graphite boat, placed in a tubular atmosphere furnace, and heated to 1550°C at a rate of 2°C / min under an argon atmosphere. The carbonization was performed for 2 hours and the mixture was naturally cooled to room temperature to obtain coal-based hard carbon.

[0070] Comparative Example 4

[0071] (1) The collected sun-dried grapefruit peel was crushed in a wall-breaking machine, passed through a 300-mesh sieve, and the D50 was 40 μm, and then dried in a forced air oven at 80°C for 12 h. 10 g of grapefruit peel powder was placed in an alumina porcelain boat, placed in a tubular atmosphere furnace, and heated to 500°C at a rate of 5°C / min in an air atmosphere.

[0072] (2) Take out the grapefruit peel powder after carbonization pretreatment, put it into 1M NaOH solution, and treat it with alkali at 50°C for 5h. Then filter, wash and dry. Put the grapefruit peel powder after alkali treatment into 2M HCl solution, stir at room temperature for 5h, filter, wash and dry.

[0073] (3) The grapefruit peel after carbonization pretreatment, alkali treatment and acid treatment was placed in a graphite boat, placed in a tubular atmosphere furnace, and heated to 1550°C at a rate of 2°C / min under an argon atmosphere. The carbonization was performed for 2 h and the mixture was naturally cooled to room temperature to obtain grapefruit peel-based hard carbon.

[0074] Effect Example

[0075] (1) SEM test

[0076] The walnut green peel-based hard carbon of Example 1 was subjected to SEM detection. Figure 1 It can be observed that the walnut green peel-based hard carbon structure of Example 1 is dense and compact, and there are obvious honeycomb structures remaining on the surface. These structures provide fast channels for sodium ions and ensure its rate performance.

[0077] (2) XRD test

[0078] The walnut green peel-based hard carbon of Example 1 and Comparative Example 1 was subjected to XRD test, and the (002) interplanar spacing was calculated according to the Bragg diffraction equation. The specific data are shown in Table 1. The interplanar spacing of Example 1 is smaller than that of Comparative Examples 1 and 2. Figure 2 As shown, the broad peak of the (002) crystal plane of the sample of Example 1 is shifted to the right compared with the sample of Comparative Example 1, indicating that the interlayer spacing is decreasing, and the (002) peak of Example 1 is sharper in comparison, indicating that its graphite microcrystal area is increasing, which is consistent with the purpose of the modification.

[0079] (3) Specific surface area test

[0080] The nitrogen adsorption and desorption BET test was performed on the walnut green peel-based hard carbon of Example 1 and Comparative Examples 1-2. As shown in Table 1, the specific surface areas of Example 1 and Comparative Examples 1-2 are 8.9934 m 2 / g, 24.1779m 2 / g, 32.1417m 2 / g. It is the combined effect of high temperature carbonization and graphite boat that makes it show a lower specific surface area.

[0081] (4) Raman test

[0082] Raman spectroscopy analysis was performed on the walnut green peel-based hard carbon of Example 1 and Comparative Examples 1-2. ID / IG is the ratio of the Raman scattering light intensity of the D peak and the G peak after the Raman spectrum is normalized by removing the baseline (D peak represents defects or disordered structures, which are related to the degree of defects in the material; G peak represents the ordered graphitized carbon crystal structure characteristics), and ID / IG represents the degree of defects and disorder of the material. From Table 1, it can be seen that the material disorder of Example 1 is the lowest, indicating that its local graphitization degree is higher and there are more graphite microcrystalline structures.

[0083] Table 1 Comparison of physical and chemical parameters of walnut green peel hard carbon of embodiment and comparative example

[0084]

[0085] (5) XPS spectrum test

[0086] XPS energy spectrum analysis was performed on the walnut green peel-based hard carbon of Example 1 and Comparative Example 1. Figure 3 The high-resolution XPS energy spectrum of C1s of the two samples can clearly identify four main peaks through fitting analysis, which are located at 284eV, 284.8eV, 286eV and 288.5eV respectively. These four main peaks correspond to different chemical bonding states, namely sp2 hybridized carbon, sp3 hybridized carbon, CO bond and O=CO bond. By observing the energy spectrum, it can be found that the content of sp2 hybridized carbon has increased significantly in the walnut green peel-based hard carbon of Example 1. This observation result is mutually confirmed by the results of XRD and Raman tests. The crystal phase epitaxy of the graphite boat under high-temperature carbonization makes its graphite microcrystalline structure grow significantly, indicating that the preparation method of the present invention makes the prepared walnut green peel-based hard carbon have a high platform capacity.

[0087] (6) Electrochemical performance test

[0088] The electrochemical performance of the walnut green peel-based hard carbon of Example 1 and Comparative Examples 1-2, the coal-based hard carbon of Comparative Example 3, and the grapefruit peel-based hard carbon of Comparative Example 4 was tested, and the test method was as follows:

[0089] Electrode preparation: The walnut peel-based hard carbon of Example 1 and Comparative Examples 1-2, the coal-based hard carbon of Comparative Example 3 and the grapefruit peel-based hard carbon of Comparative Example 4, conductive carbon (Super P) and a binder (1:1 sodium carboxymethyl cellulose and styrene-butadiene rubber solution dissolved in water) were uniformly mixed in a ratio of 8:1:1 to form a slurry and coated on copper foil. Then, the copper foil was placed in a vacuum oven and dried at 80°C for 12 hours. Take out the dried electrode and put it into a roller press to roll it to a compacted thickness of 75% of the original thickness. The electrode was punched into a disc with a diameter of 13 mm. The active material loading of the electrode was about 1.8 mg / cm 2 .

[0090] Battery assembly: The negative electrode is a metal sodium sheet (diameter, thickness), the positive electrode is a prepared electrode sheet, the electrolyte is 1molL-1NaClO4 / PC, and the glass fiber (Whatman GF / A) is used as the separator. It is assembled into a 2032-type button battery in a glove box filled with Ar atmosphere (O2<0.1ppm, H2O<0.1ppm).

[0091] The battery performance test was carried out in the voltage range of 0.001-2.5V using the LAND-CT2001A battery system. Among them, the calculation of the slope capacity and the platform capacity is calculated according to the second-cycle discharge specific capacity. The slope capacity refers to the capacity corresponding to the slope portion of the voltage curve during the discharge process, and the voltage of this portion is above the platform voltage range, in the higher voltage range (>0.1V vs Na / Na+). The platform capacity refers to the capacity corresponding to the voltage platform portion during the discharge process, and the voltage of this portion is located in the lower voltage range (0.1–0.01V vs Na / Na+). A higher platform capacity helps to increase the voltage window of the full battery, thereby improving the energy density of the sodium ion battery. The specific electrochemical performance data of Example 1 and Comparative Examples 1-4 are shown in Table 2.

[0092] Figure 4The first cycle charge and discharge curves of the battery made of walnut green peel-based hard carbon of Example 1 and Comparative Example 1 under 20mA / g conditions show that the platform capacity of the modified sample has increased significantly, and its first cycle charge capacity has reached 314.5mAh / g, and the coulombic efficiency has also been improved to 93.21%, which comes from its lower surface defects and specific surface area. The platform capacity and slope capacity of the two samples were counted from the discharge curve of the second cycle. The platform capacity of the sample in Example 1 reached 252.4mAh / g, which increased by 52mAh / g compared to 200.4mAh / g of Comparative Example 1, indicating that the technical solution of the present invention has prepared walnut green peel-based hard carbon with a large platform capacity.

[0093] Figure 5 The long cycle performance data of the samples of Example 1 and Comparative Example 1. At a current density of 0.1A / g, the sample of Example 1 can still maintain a specific capacity of 282mAh / g, and the specific capacity of Comparative Example 1 is 261mAh / g. After 100 cycles, the capacity retention rates of the two are 94.9% and 93.8%. The sample of Example 1 shows better long cycle stability and capacity retention rate.

[0094] Figure 6 The figure is the rate performance diagram of the samples of Example 1 and Comparative Example 1. The samples of Example 1 and Comparative Example 1 reached 210 mAh / g and 198 mAh / g respectively at a large current density of 2000 mA / g, and the walnut green peel biomass hard carbon showed excellent rate performance. This shows that due to the unique 3D structure of the walnut green peel-based hard carbon of the present invention, the electrolyte can quickly enter the interior of the electrode, and there are more sodium ion transmission channels, which can achieve rapid transmission of sodium ions.

[0095] Table 2 Comparison of electrochemical properties of walnut green skin hard carbon of the embodiment and the comparative example

[0096]

[0097] According to the data in Table 1 and Table 2, there are obvious differences between the embodiment and comparative examples 1 and 2 in charge and discharge specific capacity, platform capacity and microstructure. The charge and discharge specific capacity of embodiment 1 is higher than that of comparative examples 1 and 2, indicating that its electrochemical performance is better. Although the charge and discharge specific capacity of comparative example 2 is improved compared with that of comparative example 1, the improvement of platform capacity is still not significant. The first-cycle platform capacity of embodiment 1 is significantly larger, indicating that it has stronger potential in sodium ion battery applications.

[0098] In terms of microstructure, Example 1 has a lower specific surface area, but its ID / IG ratio and the interlayer spacing of the 002 peak are more moderate than those of Comparative Examples 1 and 2. Comparative Example 2 has increased specific surface area and defect level, but has not significantly improved the platform capacity, indicating that simply relying on the improvement of these microstructural characteristics is not enough to improve the overall performance of the battery.

[0099] In general, Example 1 is more effective in optimizing carbonization temperature and microstructure, while Comparative Examples 1 and 2, although different in specific surface area and degree of defects, fail to significantly improve platform capacity and electrochemical performance. This shows that to achieve ideal electrochemical performance, a higher carbonization temperature and more comprehensive structural optimization are required to achieve better results.

[0100] According to the data in Table 2, compared with Example 1 and Comparative Examples 3-4, Example 1 is superior to the coal-based hard carbon of Comparative Example 3 and the grapefruit peel-based hard carbon of Comparative Example 4 in terms of initial charge and discharge specific capacity, coulomb efficiency, and platform capacity, which shows that the scheme of the present invention is specifically optimized for walnut green peel, and solves the electrochemical performance problem caused by the complex chemical components such as cellulose, lignin, and organic acid in the carbonization process. The preparation method of the present invention stimulates the potential of walnut green peel in battery applications, making it show stronger advantages compared with other biomass materials.

Claims

1. A method for preparing walnut green peel-based hard carbon, characterized in that: It includes the following steps: The walnut green peel is carbonized after being subjected to carbonization pretreatment, alkali treatment and acid treatment, and then contacted with a graphite boat; The end point temperature of the carbonization is 1500°C-1600°C; The heat preservation time of the carbonization is 1h-5h.

2. The method for preparing walnut green peel-based hard carbon according to claim 1, characterized in that: The walnut green husk is the walnut green husk that has been subjected to one or more of a crushing treatment, a screening treatment or a drying treatment.

3. The method for preparing walnut green peel-based hard carbon according to claim 2, characterized in that: The crushing equipment is a wall breaking machine; And / or, the median particle size D50 of the product obtained after the pulverization process is 35 μm-45 μm, for example 40 μm; And / or, the mesh size of the sieve used in the sieving process is 250-350 mesh, for example, 300 mesh; And / or, the drying equipment is a blower; And / or, the drying temperature is 80°C-120°C; And / or, the drying time is 6h-24h, for example 12h.

4. The method for preparing walnut green peel-based hard carbon according to claim 1, characterized in that: The carbonization pretreatment device is a tubular atmosphere furnace; And / or, during the carbonization pretreatment process, the container for holding the walnut green peel is an alumina porcelain boat; And / or, the end temperature of the carbonization pretreatment is 450°C-750°C, preferably 500°C-600°C; And / or, the atmosphere of the carbonization pretreatment is air; and / or, the heating rate from room temperature to the end temperature of the carbonization pretreatment is 1°C / min-10°C / min, preferably 2°C / min-5°C / min; And / or, the heat preservation time of the carbonization pretreatment is 1h-10h, preferably 2h-4h.

5. The method for preparing walnut green peel-based hard carbon according to claim 1, characterized in that: In the alkaline treatment, the concentration of the alkaline solution is 1M-5M; Preferably, the concentration of the alkaline solution is 1M-2M; Preferably, the alkaline solution is sodium hydroxide or potassium hydroxide; And / or, the temperature of the alkali treatment is 50°C-90°C, preferably 50-60°C; And / or, the alkali treatment time is 1h-5h, preferably 4h-5h.

6. The method for preparing walnut green peel-based hard carbon according to claim 1, characterized in that: In the acid treatment, the concentration of the acid solution is 1M-5M; Preferably, the concentration of the acidic solution is 2M-3M; Preferably, the acidic solution is hydrochloric acid or sulfuric acid; And / or, the acid treatment time is 1 h-6 h, preferably 5 h-6 h.

7. The method for preparing walnut green peel-based hard carbon according to claim 1, characterized in that: The carbonization device is a tubular atmosphere furnace; And / or, the end point temperature of the carbonization is 1550°C-1600°C; And / or, the carbonization atmosphere is an inert atmosphere, preferably argon; and / or, the heating rate from room temperature to the end temperature of the carbonization is 1°C / min-8°C / min, preferably 2°C / min-5°C / min; And / or, the carbonization insulation time is 2h-3h.

8. A walnut green peel-based hard carbon prepared by the method for preparing walnut green peel-based hard carbon as described in any one of claims 1 to 7.

9. A pole piece, characterized in that: It comprises the walnut green peel-based hard carbon as described in claim 8.

10. Use of the electrode piece according to claim 9 in an electrochemical device.